Comparison of flipped learning and traditional lecture method for teaching digestive system diseases in undergraduate medicine: A prospective non-randomized controlled trial. (3rd April 2021) - Hernández-Guerra, Manuel; Quintero, Enrique; Morales-Arráez, Dalia Elena; Carrillo-Pallarés, Angel; Nicolás-Pérez, David; Carrillo-Palau, Marta; Gimeno-García, Antonio; González-Alayón, Carlos; Alarcón, Onofre; Otón-Nieto, Elena; Díaz-Luis, Hermógenes; Hernández-Siverio, Norberto; et al.
Abstract: Introduction: This study examined the effects of a large-scale flipped learning (FL) approach in an undergraduate course of Digestive System Diseases. Methods: This prospective non-randomized trial recruited 404 students over three academic years. In 2016, the course was taught entirely in a Traditional Lecture (TL) style, in 2017 half of the course (Medical topics) was replaced by FL while the remaining half (Surgical topics) was taught by TL and in 2018, the whole course was taught entirely by FL. Academic performance, class attendance and student's satisfaction surveys were compared between cohorts. Results: Test scores were higher in the FL module (Medical) than in the TL module (Surgical) in the 2017 cohort but were not different when both components were taught entirely by TL (2016) or by FL (2018). Also, FL increased the probability of reaching superior grades (scores >7.0) and improved class attendance and students' satisfaction. Conclusion: The holistic FL model is more effective for teaching undergraduate clinical gastroenterology compared to traditional teaching methods and has a positive impact on classroom attendances.